MicroRNA-27a/b controls endothelial cell repulsion and angiogenesis by targeting semaphorin 6A - Urbich, Carmen; Bennewitz, Katrin; Kroll, Jens (Blood, 2012)
MicroRNAs (miRs) are small RNAs that regulate gene expression at the posttranscriptional level. miR-27 is expressed in endothelial cells, but the specific functions of miR-27b and its family member miR-27a are largely unknown. Here we demonstrate that overexpression of miR-27a and miR-27b significantly increased endothelial cell sprouting. Inhibition of both miR-27a and miR-27b impaired endothelial cell sprout formation and induced endothelial cell repulsion in vitro. In vivo, inhibition of miR-27a/b decreased the number of perfused vessels in Matrigel plugs and impaired embryonic vessel formation in zebrafish. Mechanistically, miR-27 regulated the expression of the angiogenesis inhibitor semaphorin 6A (SEMA6A) in vitro and in vivo and targeted the 3′-untranslated region of SEMA6A. Silencing of SEMA6A partially reversed the inhibition of endothelial cell sprouting and abrogated the repulsion of endothelial cells mediated by miR-27a/b inhibition, indicating that SEMA6A is a functionally relevant miR-27 downstream target regulating endothelial cell repulsion. In summary, we show that miR-27a/b promotes angiogenesis by targeting the angiogenesis inhibitor SEMA6A, which controls repulsion of neighboring endothelial cells.
Prepublished online as Blood first edition paper, December 19, 2011
Gesehen am 21.02.2019